Student evaluation of faculty performance - Robert V. Supple (Educational Considerations, 1979)
The purpose of this study was to determine the relationship of students' attitudes toward evaluation of a modular program in Foundations of Education sponsored by the College of Education of the University of Maine at Orono, Maine.